Prevalence of non-compliance to prescribed antihypertensive medication among hypertensive middle-aged adults at a tertiary care hospital, Faisalabad, Pakistan: a descriptive cross-sectional study. - Sana Liaqat; Kamran Afzal; Afsar Ali; Umair Arif; Shagufta Parveen (Journal of University Medical & Dental College, 2024)
ABSTRACTBACKGROUND & OBJECTIVE: Uncontrolled hypertension due to non-compliance with prescribed treatment is one of the main reasons for premature illness and mortality in Pakistan. There is a lack of data on the prevalence of non-compliance with prescribed antihypertensive therapy among hypertensive middle-aged adults in Pakistan. To determine the overall prevalence of non-compliance with prescribed antihypertensive medication among middle-aged hypertensive patients at a tertiary care hospital in Faisalabad, Pakistan.METHODOLOGY: A Descriptive cross-sectional study was conducted over six months from December 2023 to May 2024. All hypertensive patients aged between 40 and 59 years who are conveniently available are included in this study. Data were directly collected from participants by using a structured questionnaire Hill-Bone Medication Adherence Scale. Informed consent was obtained, and participants were briefed on the research topic. The researcher explained the questionnaire in Urdu, which was completed in their presence, ensuring confidentiality to respect participants' ethical rights.RESULTS: A non-compliance score below 25 suggests a low non-compliance rate of 1.56%. Scores between 25-35 indicate moderate non-compliance at 8.31%. Scores of 35-45 show substantial non-compliance with a rate of 62.86%. Severe non-compliance, with scores above 45, results in a high rate of 27.27%.CONCLUSION: The study reveals varying compliance levels among hypertensive patients, highlighting minimal to severe non-compliance, necessitating targeted interventions to reduce non-compliance rates.